2019
DOI: 10.37358/mp.19.1.5119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Plastic Materials as a New Source of Energy

Abstract: The pyrolysis can be an attractive way to reduce the plastic waste and, in the same time, to obtain alternative conventional fuels. In this respect, four polymers (low-density polyethylene, high-density polyethylene, propylene and polystyrene) were used in the pyrolysis process. The experiments were carried out by using an in-house plant, which allowed a maximum test temperature of 450 �C. The product oil and the derived gas from the pyrolysis process were evaluated using different techniques, such as elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 10 publications
4
28
0
Order By: Relevance
“…Thus, the use of these pyrolysis oils for energy purposes, either in their natural form or transformed by fractional distillation into fuels, cannot be ignored. The HHV recorded for the SSPyOil, obtained with a heating rate of 10ºC/min, namely 8126 kcal/kg, was similar to the values presented in literature [1,11,12,35,36] and in some cases being even double [11,33]. In contrast, the concentration of N and S, two elements with high potential for negative environmental impact, through the formation of gaseous oxides, such as SOx and NOx, after the oils combustion, were higher than the data reported in literature, namely, for N it was obtained 6.00 wt% in this study in comparison with 1.50 -5.60 wt% [33,37] and for S it was obtained 1.20 wt% in this study in comparison with 0.43 -0.50 wt% [33,34].…”
Section: Sspyoil Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, the use of these pyrolysis oils for energy purposes, either in their natural form or transformed by fractional distillation into fuels, cannot be ignored. The HHV recorded for the SSPyOil, obtained with a heating rate of 10ºC/min, namely 8126 kcal/kg, was similar to the values presented in literature [1,11,12,35,36] and in some cases being even double [11,33]. In contrast, the concentration of N and S, two elements with high potential for negative environmental impact, through the formation of gaseous oxides, such as SOx and NOx, after the oils combustion, were higher than the data reported in literature, namely, for N it was obtained 6.00 wt% in this study in comparison with 1.50 -5.60 wt% [33,37] and for S it was obtained 1.20 wt% in this study in comparison with 0.43 -0.50 wt% [33,34].…”
Section: Sspyoil Propertiessupporting
confidence: 87%
“…Comparing the HHV of oils obtained in this work with the data reported in literature of conventional liquid fuels [35], such as gasoline, kerosene, diesel and heavy fuel oil (Table 5), it can be observed that are similar. The investigation of metals content in SS is very important, therefore Table 6 reveals the metal concentrations found in pyrolysis oils, but also in different types of liquid fuels from various studies [35,38]. Table 6.…”
Section: Sspyoil Propertiessupporting
confidence: 69%
See 1 more Smart Citation
“…Compositional characterization of the oils obtained in the pyrolysis processes was achieved using an elemental analyser, Flash EA 2000 (Thermo Scientific, UK). PPO samples were introduced into special tungsten -silver nacelles, subjected to combustion-pyrolysis at extremely high temperatures of 950 °C -1050 °C; the resulting gases (CO2, NO2, SO2, H2O, CO) passed a quartz reactor with a special filler, then the gas chromatographic columns with SM5A -Porapak Q filler, and detected by a thermal conductivity detector -TCD [24]. Calibration of the elemental analyser was performed with 2.0-3.0 mg of BBOT (C: 72.58 wt.%, H: 6.09 wt.%, S: 7.43 wt.%, O: 7.41 wt.% and N: 6.54 wt.%), an amino acid traceable to NIST.…”
Section: Experimental Part Materials Methods and Apparatusmentioning
confidence: 99%
“…Some authors propose new approaches and energy solutions for the power supply of EV-CS, by integrating new technologies for electricity production, especially hydrogen energy. [36][37][38][39][40] Xu et al 39 introduce a unique concept to provide, in the same location, both the electric charging of the electric vehicles and the hydrogen supply of fuel cell vehicles. Mehrjerdi conducts a study on the optimal cooperation of solar panels, hydrogen storage system, water electrolyzer, fuel cells, and diesel generator with the goal of fuelling at the same time electric vehicles and hydrogen vehicles.…”
Section: Introductionmentioning
confidence: 99%